Control Based on Feedback Linearization of a Mobile Manipulator Robot for Trajectory Tracking - Iknı, Samir; Achour, Abdelyazid (Fırat University, 2022)
The use of robotic systems has now become almost necessary in various fields. Of which, the realization of any hard or dangerous place requiring an implication of manipulation and locomotion, is necessarily entrusted to a mobile manipulator. In this work, we present a control approach that ensures the stability of the system, based on the linearization of feedback. We have determined the kinematic and dynamic models in order to apply the control with a high degree of accuracy. The approach is validated by simulation tests.
Keywords: Engineering; Mühendislik